Outcome Assessment and Impact Estimation: FTA’s Research Contributions to Address Widespread Unsustainable Land Use Practices (Challenge 3) - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The study “Outcome Assessment and Impact Estimation: FTA’s Research Contributions Addressing Widespread Unsustainable Land Use Practices (Challenge 3)” is part of a series of integrative studies assessing the contributions of the Forests, Trees and Agroforestry (FTA) CGIAR Research Program (CRP) since the program’s inception in 2011. This evaluation features research undertaken as part of the FTA program , led by FTA partner institutions (Center for International Forestry Research (CIFOR), World Agroforestry (ICRAF), Bioversity International, the French Agricultural Research Centre for International Development (CIRAD), the Tropical Agricultural Research and Higher Education Center (CATIE), the International Network for Bamboo and Rattan (INBAR), and Tropenbos International) and/or other international and national partners.